2019
DOI: 10.1029/2019gl084833
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations of Titan's Brightness

Abstract: The absolute brightness of astronomical bodies can be represented by the emitted power, which plays important roles in their radiated energy budgets. The Cassini observations include three seasons of Titan, which provides an unprecedented opportunity to examine the seasonal variations of Titan's emitted power. Our analyses show that Titan's emitted power displays different seasonal behaviors between the Northern Hemisphere and the Southern Hemisphere. The global-average emitted power decreased by 6.8 ± 0.4% du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…These predictions, along with inferences of temperature from in situ density profiles obtained with the Cassini Ion and Neutral Mass Spectrometer (INMS) and Huygens Atmospheric Structure Instrument (HASI) and measurements derived through stellar occultations from the ground and the Cassini Ultraviolet Imaging Spectrograph (UVIS), revealed large variability in Titan's middle and upper atmospheric thermal structure on both diurnal and seasonal timescales. Further, observations from the Cassini Composite Infrared Spectrometer (CIRS), Imaging Science Subsystem (ISS), and Visible and Infrared Mapping Spectrometer (VIMS) instruments covering roughly half a Titan year indicated that Titan's radiative energy budget may not be fully balanced on both temporal (seasonal) and spatial (hemispheric) scales (Li 2015;Creecy et al 2019Creecy et al , 2021, though further observations are required to determine the nature and effects of this imbalance on timescales of a Titan year or more.…”
Section: Introductionmentioning
confidence: 99%
“…These predictions, along with inferences of temperature from in situ density profiles obtained with the Cassini Ion and Neutral Mass Spectrometer (INMS) and Huygens Atmospheric Structure Instrument (HASI) and measurements derived through stellar occultations from the ground and the Cassini Ultraviolet Imaging Spectrograph (UVIS), revealed large variability in Titan's middle and upper atmospheric thermal structure on both diurnal and seasonal timescales. Further, observations from the Cassini Composite Infrared Spectrometer (CIRS), Imaging Science Subsystem (ISS), and Visible and Infrared Mapping Spectrometer (VIMS) instruments covering roughly half a Titan year indicated that Titan's radiative energy budget may not be fully balanced on both temporal (seasonal) and spatial (hemispheric) scales (Li 2015;Creecy et al 2019Creecy et al , 2021, though further observations are required to determine the nature and effects of this imbalance on timescales of a Titan year or more.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 shows the comparison between the absorbed power from this study and the emitted power measured in our previous study (Creecy et al., 2019). The decrease in the absorbed power (18.7% ± 0.5%) is much stronger than the decrease of emitted power (6.8 ± 0.4%) for the Cassini epoch.…”
Section: Resultsmentioning
confidence: 74%
“…(a) Comparison between the absorbed solar power (red line) and the emitted thermal power (blue line). The measurements of Titan's emitted power are from our previous study (Creecy et al., 2019). (b) The ratio between the net radiant energy (i.e., absorbed power‐emitted power).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations